Optical properties of single crystals and ceramics based on silver and thallium (I) halides in the range of 0.3–30.0 THz - Pestereva, P.; Yuzhakova, A.; Lvov, A.; Salimgareev, D.; Yudin, Nikolay N.; Voevodin, Vladimir I.; Sarkisov, Sergey Yu; Korsakov, A.; Zhukova, L. (Infrared physics and technology)
This paper is devoted to single crystals and two-phase ceramics based on the TlBr0.46I0.54 – AgI, TlCl0.74Br0.26 – AgI, AgBr – AgI systems' properties study in the THz range of 0.3–30.0 THz. Plane-parallel windows were manufactured based on single crystals of composition 6, 13 mol.% AgI in TlBr0.46I0.54 and 3, 13, 25 mol.% AgI in AgBr, as well as based on two-phase ceramic composition 19, 25 mol.% AgI in TlBr0.46I0.54, 7, 14, 20, 27 mol.% AgI in TlCl0.74Br0.26 and 36 mol.% AgI in AgBr. The materials showed high transmission in the THz with an absorption band. Single crystals and ceramics of the TlBr0.46I0.54 – AgI system are transparent in the ranges 0.3–0.67 and 5–30 THz, which corresponds to wavelengths 447–1000 μm and 10–60 μm. The maximum transparency of the materials in the 5–30 THz range is 70 %, in the other ranges it reaches 40 %. Ceramics of the TlCl0.74Br0.26 – AgI system transmit THz radiation in the 0.3–0.85 and 6–30 THz (353–1000 μm and 10–50 μm) regions. The transparency reaches 60 % in the frequency range of 0.3–0.85 THz and 77 % in the range of 6–30 THz. In the case of AgBr – AgI system, the samples were transparent from 0.3 to 1 THz (300–1000 μm) with a maximum transparency of 77 % and from 5.55 to 30 THz (10–54 μm) with transparency up to 60 %. The attenuation coefficients for each system were quite low 0.03–0.8 cm−1 depending on the composition and system. The value of the coefficients decreased with decreasing emission frequency. The paper also compares the developed THz materials with known materials. A multiple characterization of each class of THz optical materials is given. As a result of the studies, it is found that the set of obtained properties makes the developed THz materials based on silver halides and monovalent thallium halides promising potential materials for application in THz devices and devices for a wide range of purposes.